ANALISIS NILAI PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DI BURSA EFEK INDONESIA - Sylviana Marzza Dwi Susanty, (2022)
The purposes of this research are to assess the effect of Profitability, Leverage, Firm Size, and Business Risk on Company Value. The population is all companies which engaged in the field of primary consumer goods listed in Indonesia Stock Exchange (IDX). By using slovin sampling, obtained 47 primary consumer goods with research period of five years to obtain 232 sample unit. Data analysis has been carried out by using panel data regression analysis with Eviews 12 and significant level 10%. The result of this research show that Profitability as measured by Return on Asset (ROA) does not give any influence to the Company Value, Leverage as measured by Debt to Asset Ratio (DAR) give positive influence to the Company Value, Firm Size as measured by SIZE does not give any influence to the Company Value, and Business Risk as measured by Business Risk (BRISK) does not give any influence to the Company Value.